TWO-STEP PROCESS FOR PRODUCING HIGH YIELDS OF OIL FROM BIOMASS - BARTEK, ROBERT; HEINERMAN, JACOBUS, JOHANNES LEONARDUS; CERQUEIRA, HENRIQUE, S; O'CONNOR, PAUL; SANCHEZ IGLESIAS, VICENTE (2011)
A process is disclosed for preparing a bio-oil having a Total Acid number ("TAN") of less than 10. The process comprises the steps of:(i) subjecting the solid biomass material to a catalytic pyrolysis process whereby a bio-oil having a TAN of less than 60 and greater than 10 is produced; and (ii) subjecting the bio-oil obtained in step (i) to an acid removal step. Significant TAN gains can be made by separating the hydrophobic phase of the bio-oil from the aqueous phase. Each phase can be subjected to a removal of acidic components by physical adsorption, chemisorption, extraction, neutralization, or chemical conversion. La présente invention concerne un procédé pour préparer une huile biologique ayant un indice d'acide total (« TAN ») inférieur à 10. Le procédé comprend les étapes consistant à : (i) soumettre le matériau de biomasse solide à un traitement de pyrolyse catalytique de telle manière qu'une huile biologique ayant un TAN inférieur à 60 et supérieur à 10 soit produite ; et (ii) soumettre l'huile biologique obtenue dans l'étape (i) à une étape d'élimination d'acide. Des gains significatifs de TAN peuvent être réalisés en séparant la phase hydrophobe de l'huile biologique de la phase aqueuse. Chaque phase peut être soumise à une élimination de composants acides par adsorption physique, chimisorption, extraction, neutralisation, ou conversion chimique.